Ultra-Fast Wiener Filter Based Crystal Identification Algorithm Applied to the Labpet Phoswich Detectors - Yousefzadeh, H. Camilia; Viscogliosi, Nicolas; Tétrault, Marc-André; Semmaoui, Hicham; Pepin, Catherine M.; Bérard, Philippe; Bergeron, Mélanie; Lecompte, Roger; Fontaine, Réjean (CMBES Proceedings, 2008)
No Abstract